Optimizing an Injectable Composite Oxygen-Generating System for Relieving Tissue Hypoxia - Hsieh, Tai-En; Lin, Sheng-Ju; Chen, Li-Chi; Chen, Chun-Chieh; Lai, Po-Liang; Huang, Chieh-Cheng (Frontiers in Bioengineering and Biotechnology, 2020)
Oxygen deficiency resulting from bone fracture-induced vascular disruption leads to massive cell death and delayed osteoblast differentiation, ultimately impairing new bone formation and fracture healing.Enhancing local tissue oxygenation can help promote bone regeneration. In this work, a composite oxygen-generating system consisting of calcium peroxide (CaO2)/manganese dioxide (MnO2)-encapsulated poly lactic-co-glycolic acid (PLGA) microparticles (CaO2 + MnO2@PLGA MPs) is proposed for the local delivery of oxygen. By utilizing a series of methodologies, the impacts of each component used for MP fabrication on the oxygen release behavior and cytotoxicity of the CaO2 + MnO2@ PLGA MPs are thoroughly investigated. Our analytical data obtained from in vitro studies indicate that the optimized CaO2 + MnO2@PLGA MPs developed in this study can effectively relieve the hypoxia of preosteoblast MC3T3-E1 cells that are grown under low oxygen tension, thus holding great promise in enhancing fractural healing by increasing tissue oxygenation.